Characterization of vitelline vessel remnant circulation in the umbilical cord. (August 2021) - De Guzman, John Kemuel; Yu, Weiming; Horn, Christopher; Brundler, Marie-Anne; Wright, James R.
Abstract: The vitelline circulation normally regresses by about 10 weeks gestation. Vitelline vessel remnants (VVRs) are found in approximately 4–11% of umbilical cords. While these remnants retain an active fetal circulation, this has never been studied. Using an operating microscope, VVRs were catheterized, injected with ink, and then examined grossly and histologically. Over 90% of VVRs are paired thin-walled vessels with afferent and efferent circulation completed within the cord via capillary plexuses and bridging vessels; <10% are single thin-walled arterial vessels running the length of the cord to the placental disc, with their venous return circulation via allantoic umbilical vessels. Highlights: Vitelline vessel remnants (VVRs) are found in 4–11% of umbilical cords. VVRs exist as paired (~90%) or unpaired (<10%) thin-walled vessels. Paired VVR circulatory loops involve capillary plexuses within cords. Unpaired VVRs extend the full length of the cord and onto the placental disc. Venous return to the fetus for unpaired VVRs is via allantoic circulation.